Strengthening Sharia Bank Operational Management Through Internalization of Sharia Compliance - Hozinul Asror; Mugiyati (International Journal of Economics Accounting and Management, 2025)
This study aims to analyse the strengthening of Islamic bank operational management through the internalisation of Shariah compliance as a strategic instrument, not merely as a normative obligation. The method used is a literature review of various previous studies, regulations, and implementation practices in Indonesian Islamic banking. The results of the analysis show that the internalisation of Shariah compliance can be realised through five main strategies, namely strengthening the competence and independence of the Shariah Supervisory Board (DPS), utilising service digitalisation, increasing Shariah financial literacy, improving regulations related to DPS opinions, and integrating digitalisation with aspects of customer security and trust. These findings confirm that Shariah compliance not only serves to ensure the conformity of products and transactions with Islamic law, but also strengthens governance, operational effectiveness, and the competitiveness of the Islamic banking industry. Thus, this study concludes that the internalisation of Shariah compliance is key to maintaining the integrity of Shariah principles while promoting sustainability and public trust in Islamic banks in Indonesia.